Licensing Innovations in Improving Regional Investment in Boyolali Regency - Suhendra, Adi (Jurnal Bina Praja, 2018)
Ease of investing supports the competitiveness of the region. Currently the licensing process in Boyolali Distric has a number of problems, among others, not all head of regions/head of Departments agree to delegate their authority to the head of Department of the One Stop Integrated Service (DPM-PTSP), insufficient human resources, and conflict between the licensing agency in the region with the technical unit (formed by the decision of the District Head that consists of elements of the related Regional Work Unit in charge of carrying out the field examination, technical discussion and provide recommendations/considerations regarding a license). The purpose of this study is to describe the efforts of the regional government in solving problems in the delegation of authority to the DPM-PTSP, overcoming the limitation of human resources and the conflict between the technical unit of the licensing services, transparency, accountability and certainty for the applicant. This study is using the qualitative case study approach. Data collection methods were conducted through in-depth interviews, secondary data and field observations. For the validity of the data, the researchers perform data triangulation. The sources of this study are the Head of Boyolali District, the Head of DPMPTSP and its officers. For data processing, the researchers perform open coding, axial coding and selective coding. The findings of this research are that some of the problem are solved by issuing the Boyolali Head of District Regulation Number 10 of 2013 Regarding Implementation Guideline of the Head of District Regulation Number 4 of 2012 (on the Integrated Licensing and Non-Licensing of Boyolali District) to delegate the District Head authority and synchronize the OPD. To overcome the limitations of their human resources, an online licensing application was created to provide an effective and efficient licensing process in Boyolali District.